Pelatihan Video Shooting & Editing Untuk Santri Muda Pondok Pesantren Tahfizhul Qur'an Tajul Qurani - Parlindungan Ravelino; R.A Rizka Qori Yuliani Putri (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Religious education is the foundation for every human being. Islamic education is not only a complementary science, but it should be a basic science in living the life of Muslims and Muslim women. Some people on their own initiative and together with their groups feel the lack of religious knowledge in formal schools. Therefore, the emergence of Islamic Boarding Schools and Tahfidz Houses, especially in Pekanbaru, can become Al-Qur'an Educational Institutions and Islamic Da'wah / Study Institutions for the community, especially for early childhood. Tahfizhul Qur'an Islamic Boarding School Tajul Qurani is a boarding school to practice reading the Qur'an and Da'wah / Islamic Studies, initially only accepted female students, but with more and more enthusiasts who want to learn, partners also open classes for boys. Partners want to expand the symbols of Learning to read the Qur'an and Islamic Studies more broadly, namely through the YouTube channel. Partners have a lack of knowledge about how to document with video-shooting & editing media as well as effective ways to upload videos to YouTube. The target to be achieved is for partners to understand how to video-shooting & edit which will later be published through the partner's YouTube channel, and the outputs to be achieved are community learning services, reports, and scientific articles (journals)